Questões que permeiam o gênero neutro, impactam a língua portuguesa e cruzam a língua de sinais - Nery, Victor Hugo (Universidade Federal de São Carlos, 2023)
This research main objective is to establish a debate about the use of gender-neutral words in Libras, some signs that has this neutrality, as well the relation of the neutrality and minority groups. Through essay features, this work utilizes the already existing bibliography regarding the subject applied to oral languages, such as Portuguese, in order to develop the discussions, both academic and professional, around the neutrality in the Brazilian Sign Language, exposing the necessity of inclusive practices in the speech of the interpreter and translators. This essay tries to debate and think about the possibility of interpreters and translators became aware of the neutral signs, and consider them in their regular practices, adapting the speech in the act. Throughout the discussion, can be perceived that the subject is connected to an unexplored part of the deaf studies and sign languages studies. After the investigation, it is clear the absence of information and materials that discusses the subject in details.
Issues that permeate the neutral gender, impact the Portuguese language and cross sign language
Keywords: Gênero neutro; Língua de sinais; LGBTQIAPN+; Gender neutral; Sign language; LINGUISTICA, LETRAS E ARTES::LINGUISTICA